Focus on reactive nitrogen and the UN sustainable development goals - Winiwarter, Wilfried; Amon, Barbara; Bodirsky, Benjamin Leon; Friege, Henning; Geupel, Markus; Lassaletta, Luis; Raghuram, Nandula (Environmental research letters, 2022)
The scientific evidence assembled in this Focus Collection on ‘Reactive nitrogen and the UN sustainable development goals’ emphasizes the relevance of agriculture as a key sector for nitrogen application as well as its release to the environment and the observed impacts. Published work proves the multiple connections and their causality, and presents pathways to mitigate negative effects while maintaining the benefits, foremost the production of food to sustain humanity. Providing intersections from field to laboratory studies and to modelling approaches, across multiple scales and for all continents, the Collection displays an overview of the state of nitrogen science in the early 21st century. Extending science to allow for policy-relevant messages renders the evidence provided a valuable basis for a global assessment of reactive nitrogen.